Hubungan Antara Pengetahuan, Sikap, dan Perilaku Orang Tua dengan Kejadian Kekerasan Pada Anak di Kecamatan Denpasar Selatan - Ida Ayu Nyoman Santiari Andriati; Made Rismawan; Ni Komang Tri Agustini (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Violence against children continues to happen. Violence against children can be prevented if parents have a good knowledge, attitude, and behavior on preventing violence against children. The aim is to find out the correlation between parents' knowledge, attitudes, and behavior with the incidence of violence against children in South Denpasar. The research design used in this study was correlation analytic research with a cross-sectional approach. The research was conducted from March - May 2023. The sample in this study was 400 parents in the South Denpasar sub-district who had children under 18 years old and were selected through consecutive sampling. The instrument used for data collection was a self-developed questionnaire. The data were then analyzed using descriptive analysis and chi-square test. The results showed the majority of parents had moderate knowledge (40.8%), adequate attitude (44.5%), and behavior (42.8%) and had committed violence against children (336 respondents; 84%). There was a significant correlation between parents' knowledge, attitude, and behavior with the incidence of violence against children in South Denpasar District (p-value <0.001). It is necessary for parents to increase their knowledge, attitude, and behavior on violence against children. Parents are expected to be more active in obtaining information about violence against children to prevent the incidence of violence against children